Tooth‐related factors for tooth loss 20 years after active periodontal therapy–A partially prospective study. (28th August 2020) - Rahim‐Wöstefeld, Sonja; El Sayed, Nihad; Weber, Dorothea; Kaltschmitt, Jens; Bäumer, Amelie; El‐Sayed, Shirin; Eickholz, Peter; Pretzl, Bernadette
Abstract: Aim: To assess factors contributing to tooth loss 20 years after active periodontal therapy (APT) on tooth level. Materials and Methods: After an initial retrospective analysis 10 years after APT, patients were monitored for 10 more years. At clinical re‐evaluation 20 years after APT, tooth‐related factors (tooth type, location, bone loss, furcation involvement, abutment status) and patient‐related factors (gender, smoking, adherence) were investigated. Descriptive statistical analysis and a mixed logistic regression analysis were performed with tooth loss as primary outcome variable. Results: The study included 69 patients (42 female/27 male). 39 patients were non‐adherent (56.5%), and 11 were active smokers (15.9%). A total of 198 out of 1611 teeth were lost. Tooth loss was significantly highest ( p < .01 ) in molars (21.1%), multi‐rooted teeth with furcation involvement (23.5%) and abutment teeth (fixed: 27.6%, removable: 36.4%). 37.6% of teeth with initial bone loss >60% were lost during 20 years. Adherent patients showed less frequent tooth loss than non‐adherent patients (OR 0.371; p < .01 ). Conclusion: Even teeth with an initial bone loss over 60% could be retained in approximately two thirds for 20 years. This should be kept in mind when assigning prognosis and establishing a treatment plan.